Plantain (Musa spp.) cropping systems of Southern Cameroon - Hauser, S.; Amougou, D. (International Society for Horticultural Science, 2010)
Plantain (Musa spp.) cropping systems of Southern Cameroon can beseparated into those based on forest clearing and those based on land already used.Plantain is a major crop starting the forest clearing cycle. It is more than other foodcrops grown for commercial reasons. However, varietal choice for auto-consumptionis different from that for sales. Nevertheless, farmers prefer to plant mixtures ofcultivars. All systems rely on the use of natural resources with purchased inputsvirtually absent. Labor is mainly provided by household members, capital use islimited to specific operations such as tree felling, digging holes, planting andharvesting. Knowledge on pests and diseases is very limited. Farmers are unaware ofinfection pathways of nematodes such as Radopholus similis. Contrary to that,farmers are very aware of the causes of yield loss with an overall realistic assessmentof totals yield losses, estimated at 50%. The systems could be improved by simpleagronomic measures such as regular planting distances to increase densities,separation of cultivars into early versus later producing types to reduce weedinglabor. Most important appears to be raising awareness of the major pests anddiseases and simple measures to reduce or eliminate nematode and banana weevil(Cosmopolites sordidus) infestation. Research is required to determine fertilizerresponse curves, response of different plantain cultivars to planting density,response to weeding frequency and other agronomic measures to increase yields andto increase profitability.